2003
DOI: 10.1002/gene.10210
|View full text |Cite
|
Sign up to set email alerts
|

A retained selection cassette increases reporter gene expression without affecting tissue distribution in SPI3 knockout/GFP knock‐in mice

Abstract: The human serpin, proteinase inhibitor 6 (PI-6/SERPINB6), is a protease inhibitor expressed in many tissues. It inhibits a large number of proteases, including cathepsin G in granulocytes and monocytes. To determine the temporal and spatial distribution of PI-6, mice were generated in which exon 2 of the PI-6 ortholog SPI3 (Serpinb6) was replaced with a green fluorescent protein (GFP) reporter gene. This placed GFP under the control of the regulatory elements and initiation codon of the SPI3 gene. The neomycin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 24 publications
2
25
0
Order By: Relevance
“…It has been reported that retained high efficiency promoter, PGK (glycolytic enzyme phosphoglycerate kinase) could increase reporter gene expression when promoter and expression gene were located in a one transfection cassette [24]. Similarly, upon transfection, we observed a few cells (~0.1 %) presenting extremely strong constitutive EYFP signal in cells transfected with the single vector presented here.…”
Section: Resultssupporting
confidence: 60%
“…It has been reported that retained high efficiency promoter, PGK (glycolytic enzyme phosphoglycerate kinase) could increase reporter gene expression when promoter and expression gene were located in a one transfection cassette [24]. Similarly, upon transfection, we observed a few cells (~0.1 %) presenting extremely strong constitutive EYFP signal in cells transfected with the single vector presented here.…”
Section: Resultssupporting
confidence: 60%
“…3C). Opposing effects of neo cassettes on the expression of neighboring genes have previously been reported [45][46][47].…”
Section: Discussionmentioning
confidence: 81%
“…Irrespective of such unresolved issues, our stable mutant protein, which contains the integral HSR, nuclear localization signal (NLS), SAND, and truncated PHD1 domains, closely emulates the common 13-bp deletion in human APECED patients for which several studies strongly suggest the expression of a stable truncated protein (27)(28)(29). Second, the targeting vector used in the deletion of exon 6 and premature termination of the Aire protein at the end of the SAND domain in Peltonen's mice has a selection cassette that was not removable, raising the possibility of affecting the expression of neighboring genes (51)(52)(53)(54)(55)(56)(57). Third, our model allows previously unappreciated insights into the role of Aire in the maintenance of normal fertility.…”
Section: Discussionmentioning
confidence: 99%